Diversification, Strategic Groups and the Structure-Conduct- Performance Relationship: A Synthesis - Greening, Timothy (The Review of Economics and Statistics, 1980)
In recent article in this REVIEW, Howard Newman presents evidence that a complex structure of strategic groups implies competitive performance in an (1978, p. 418). Newman's evidence is necessarily limited to small sample of 34 'chemical industries because classifying an industry as homogeneous or heterogeneous with respect to its leading firms' strategies and structures is extremely time-consuming. Fortunately, Stephen Rhoades' studies of the effect of diversification on industry profits support Newman's major hypotheses for large samples of diverse manufacturing industries. Rhoades reasoned that diversification is barrier to entry because it makes predatory pricing likely and because consolidated financial reporting obscures the excess profits that normally attract entry. Therefore, Rhoades was surprised to find out that when an industry is secondary or non-primary activity for substantial portion of firms in the industry, industry margins tend to be relatively low (1973, p. 152). But this result is consistent with Newman's argument that intra-industry diversity results in more rivalrous conduct and thus competitive performance. Newman's theoretical insight explains an apparent inconsistency in Rhoades' empirical findings, and Rhoades' empirical work provides evidence that Newman's hypotheses are not peculiar to chemical process industries.